Second hepatitis C virus transmission by blood components since introduction of mandatory NAT screening in Germany. Issue 2 (14th December 2022) - Himmelsbach, Kiyoshi; Mueller, Susanne; Kress, Julia; Fiedler, Sarah A.; Miskey, Csaba; Ivics, Zoltan; Patek, Alexander; Chudy, Michael
Abstract: Background: Viral safety of blood products in Germany has improved significantly over the last two decades. We describe the second documented transfusion‐transmitted (TT) episode for the hepatitis C virus (HCV) in Germany since mandatory nucleic acid amplification techniques (NAT) screening was introduced in 1999. Study Design and Methods: When a repeat donor who had tested negative for anti‐HCV tested positive for HCV RNA by NAT in a minipool (MP) of eight, a look‐back procedure was initiated. Qualitative, quantitative and genotyping assays were used to investigate the titers of the quarantined fresh frozen plasma (FFP) from the donor and a serum sample from the recipient of the pooled platelet concentrate (PPC). Amplified products of 5'UTR and HVR1 were used for sequence comparison to characterize the HCV genomic identity of donor and recipient samples. Results: All NAT tests utilized in this procedure were able to detect a low HCV RNA titer (~15 IU/ml) in the FFP from the donation. Dilution of FFP by factor 8 was performed to mimic an MP, and the detection rate correlated well with the claimed sensitivity of the tests. Analysis of donor and recipient samples revealed genotype 3a viral transmission confirmed by sequence analysis. Conclusion: This TT HCV case could have been prevented by individual donation (ID) NAT. However, a low titer blood donation in the window period (WP) is very rare. Residual risk calculation for TT HCV in the WP revealed that, compared to MP‐NAT testing, ID‐NAT would improve blood safety only marginally.